Agrotourism Development Strategy Through SWOT Analysis in Agro Edukasi Wisata Ragunan - Fedrina, Rezka; Saira, Farah Kesya; Wicaksono, Muhammad Arif (JELAJAH: Journal of Tourism and Hospitality, 2025)
Agro Edukasi Wisata (AEW) Ragunan isaoneaofathe urban agro-tourismadestinationsathat aims to provide education about agriculture, livestock, and fisheries to the public, particularly younger generations, while also supporting food security and environmental preservation inaurbanaareas. Thisastudyawasaconductedato address challenges faced by AEW Ragunan, such as limited facilities, lack of program innovation, and insufficient promotion, which hamper its development as a competitive and sustainable educational tourism site. The research applied a descriptive qualitativeaapproach using SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis as the main framework. Primary dataawereacollectedathroughaparticipatoryaobservation, in-depthainterviews with managers and stakeholders, and documentation, while secondary data were gathered from scientific literature and official reports. The main results revealed that AEW Ragunan’s strengths include strong institutional support and a unique urban farming education concept, while its weaknesses involve limited infrastructure and marketing efforts. Opportunities exist through the growing interest in urban farming and the potential for partnerships with schools, local businesses, and government programs, whereas threats include the risk of natural disasters and a decline in visitor numbers if marketing is not strengthened. The research concludes that strategic development efforts should focus on optimizing AEW’s educational and green tourism potential, improving facilities, enhancing digital promotions, and fostering collaboration networks. Strengthening these aspects is crucial to ensuring AEW Ragunan’s sustainability and positioning it as a model for urban agro-tourism development in metropolitan cities.